PHYTOCHEMICAL SCREENING, IN VITRO ANTIOXIDANT AND ANTI PROTEASE ACTIVITIES OF METHANOLIC EXTRACT OF NILGIRIANTHUS HEYNEANUS NEES STEM - JACOB, JENSON (International Journal of Current Pharmaceutical Research, 2021)
Objective: The aim of this study was focussed on phytochemical screening, in vitro antioxidant and antiprotease activities of methanolic extract of Nilgirianthus heyneanus stem. Methods: The stem of the plant was washed thoroughly, shade dried and coarsely powdered. The powdered material of Niligirianthus heyneanus stem was extracted with methanol using soxhlet apparatus. Preliminary phytochemical screening for carbohydrates, proteins, alkaloids, phytosteroids, flavonoids, glycosides, polyphenolics, saponins, tannins was done by following standard procedure. In vitro antioxidant activities of methanolic extract were assessed using DPPH, ABTS and total antioxidant capacity. In vitro anti-protease activity of the plant was analysed using trypsin as an enzyme and BAEE (N-benzoyl-L-arginine ethyl ester) as a substrate. Results: The results showed that phytochemicals such as carbohydrates, proteins and amino acids, flavonoids, glycosides, tannins and polyphenolics are present in the methanolic extract of Niligirianthus heyneanus stem. The in vitro antioxidant and antiprotease activities of Niligirianthus heyneanus stem clearly showed that the plant has antioxidant and antiprotease activity. Conclusion: From this work, it can be concluded that Niligirianthus heyneanus stem has the potential to be a strong antioxidant and protease inhibitor.